Integration of Constitutional Law and Human Rights: A Comparative Study between Indonesia and South Africa - Sugirman, Andi; Nawawi, Jumriani; Hamzah; Amir, Irfan (Jurnal Suara Hukum, 2025)
The development of the relationship between constitutional law and human rights is fundamental in a rule of law state. Constitutional law is oriented towards regulating and simultaneously striving for the optimal protection of human rights. This research aims to examine the integration between constitutional law and human rights by conducting a comparative legal study between Indonesia and South Africa. This research is a normative legal study emphasizing historical, conceptual, legislative, and comparative legal approaches. The research findings indicate that the strengthening of human rights norms and the role of the Indonesian Constitutional Court have become crucial points, particularly the role and authority of the Indonesian Constitutional Court through its rulings aimed at protecting human rights. Similar developments also occurred in South Africa after the end of apartheid, with the establishment of the Constitutional Court and constitutional reforms as important steps in upholding the rule of law and human rights. The Constitutional Courts of Indonesia and South Africa both face issues such as weak implementation of rulings, political pressure, and slow legislative processes that accommodate the Constitutional Court's decisions. This research recommends that the integration of constitutional law and human rights should be optimized by strengthening the authority of the Constitutional Court, including the authority to ensure that Constitutional Court decisions are obeyed and implemented optimally to protect human rights.